PCI DSS : a pocket guide - Calder, Alan, 1957-; Williams, Geraint (IT Governance Publishing, 2019)
This pocket guide is perfect as a quick reference for PCI professionals, or as a handy introduction for new staff. It explains the fundamental concepts of the latest iteration of the PCI DSS, v3.2.1, making it an ideal training resource. It will teach you how to protect your customers' cardholder data with best practice from the Standard.